Elderly Diary as a Productive Activity Towards Successful Aging in the Elderly at Social Institutional - Tandipayuk, Grace; Rahmawati, Intan (Green Publisher Indonesia, 2022)
This study aims to determine successful aging in the elderly through their own stories and photos and then they can re-read the stories they told themselves previously through diary activities. This research with a qualitative approach involves two informants who are elderly and live in a nursing home. Both informants were obtained by purposive sampling technique. This study uses data collection methods by means of interviews, observations, and documentation and data analysis using thematic analysis. The results showed that successful aging can be seen from 3 factors, namely selection, optimization and compensation. Giving an elderly diary is one method that helps in opening up the elderly, becoming a forum for the elderly to refer to the extent to which the cognitive function, productive activities and physical activities of the elderly by inviting the elderly to tell their lives and attaching photos of their activities in the diary. This research only focuses on qualitative aspects and is limited to two informants. Future researchers may consider doing other methods and more informants to be involved in the research. This research contributes to the development of knowledge related to the role of productivity and cognition in the elderly. By understanding the factors of successful aging in the elderly, it helps in activating some of the roles that the elderly can still play in old age.